Biomechanical determinants of elite high jump performance in Egypt: Part 2, the percentage contributions of biomechanical indicators and special factors to achievement level - Atta, I. I.; Bursais, A. K.; Alibrahim, M. S.; Alhumaid, M. M.; Hassan, A. K.; Frikha, M.; Al-Nuaim, A. (Journal of Physical Education and Sport, 2025)
This study on high jump biomechanics was performed during the 2020 Republic Championships of Egypt, That aimed to determine the percentage contributions of biomarkers and special factors to the level of achievement. The sample consisted of 16 competitors (average weight : 87 kg, height : 1.98 m, age : 30 years). To capture three-dimensional data, Six GoProHero 6 digital cameras were used, operating at 120 frames per second. The biomechanical analysis program Skillspector was used to analyze 48 attempts, with three attempts for each athlete. A multiple regression analysis was conducted to determine the contributions of the most important biomechanical indicators as well as several special factors to performance level , Which is considered to be the key to the success of high jump education and training as it provides a clear vision for coaches to develop their training programmes. In addition to the initial push and its impact on the performance level, the study identified six indicators as special factors: the vertical kinetic energy of the body`s center of gravity at the beginning of the flight, the right wrist's net velocity at maximum knee flexion, the horizontal potential energy of the body's center of gravity at the beginning of take-off, the braking time to take-off, the net velocity of the body's center of gravity at the maximum flight altitude, and the angle of the hip joint of the take-off leg at the end of the take-off. The contribution rates of these biomechanical indicators to performance were 71%, 13%, 9%, 4%, 3%, and 1%, respectively.